2015
DOI: 10.1007/s10488-015-0709-y
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts Clinician Dropout from State-Sponsored Managing and Adapting Practice Training

Abstract: Dropouts from system-wide evidence-based practice trainings are high; yet there are few studies on what predicts dropouts. This study examined multilevel predictors of clinician dropout from a statewide training on the Managing and Adapting Practice program. Extra-organizational structural variables, intra-organizational variables and clinician variables were examined. Using multivariable logistic regression analysis, state administrative data and prospectively collected clinician participation data were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In the one pair, in which the control site outperformed the LC site, it is notable that the LC site’s clinicians were on average 20 years older. Data from the larger MAP training initiative (Olin et al, 2015) showed that age was a significant predictor of clinician dropout from MAP. Thus, this anomaly may reflect key differences in clinician characteristics (specifically age) that impacted MAP implementation; however, this issue requires further investigation in future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the one pair, in which the control site outperformed the LC site, it is notable that the LC site’s clinicians were on average 20 years older. Data from the larger MAP training initiative (Olin et al, 2015) showed that age was a significant predictor of clinician dropout from MAP. Thus, this anomaly may reflect key differences in clinician characteristics (specifically age) that impacted MAP implementation; however, this issue requires further investigation in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The EBTDC MAP program has been described in detail elsewhere (Olin et al, 2015). It included a five-day training in modular cognitive behavioral therapy and how to use the PracticeWise resources (i.e., searchable web database of evidence-based practices, practice guides, progress and outcome monitoring tools) (Chorpita, Bernstein, & Daleiden, 2008; Chorpita & Daleiden, 2009; PracticeWise, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these articles identify characteristics of the innovation as an important factor in successful implementation (Aarons et al, 2011; Rogers, 2003). Olin and colleagues (this issue) investigate outer context and inner context factors that predicted clinician drop out from a statewide training on an EBP in the State of NY, finding that younger clinicians and those that practiced in upstate-rural areas were less likely to drop out from training in an EBP. Finally, Rosen and colleagues (this issue) present a review of research focusing on the implementation of two EBPs for PTSD in the U.S. Department of Veterans Affairs.…”
Section: Brief Summary Of Articlesmentioning
confidence: 99%
“…Questions were adapted from ongoing research with New York State behavioral health agencies (Chor et al, 2014; Chor, Wisdom, Olin, Hoagwood, & Horwitz, 2015; Olin et al, 2015a, 2015b). The in-person interviews asked about barriers and facilitators to implementing and sustaining services, current and future needs of the community, local professional networks, and characteristics of an ideal services system.…”
Section: Methodsmentioning
confidence: 99%